Attitudes to disclosure of HIV-serostatus to new sexual partners and sexual behaviours among HIV-diagnosed gay, bisexual and other men who have sex with men in the UK. Issue 10 (2nd October 2020) - Daskalopoulou, Marina; Rodger, Alison J.; Phillips, Andrew N.; Gilson, Richard; Sherr, Lorraine; Wayal, Sonali; Anderson, Jane; Aderogba, Kazeem; McDonnell, Jeffrey; Wilkins, Edmund; Youssef, Elaney; Speakman, Andrew; et al.
ABSTRACT: We assessed attitudes to disclosure to new sexual partners and association with sexual behaviours among HIV-diagnosed gay, bisexual, and other men who have sex with men (GBMSM) in the UK Antiretrovirals, Sexual Transmission Risk and Attitudes (ASTRA) study in 2011-12. Among 1373 GBMSM diagnosed with HIV for ≥3 months and reporting sex in the past three months (84% on antiretroviral therapy (ART), 75% viral load (VL) ≤50c/mL), 56.3% reported higher sexual disclosure ("agree" or "tend to agree" with "I'd expect to tell a new partner I'm HIV-positive before we have sex"). GBMSM on ART with self-reported undetectable VL had lower disclosure than those on ART without self-reported undetectable VL and those not on ART. Higher sexual disclosure was associated with higher prevalence of CLS in the past three months; this was due to its association with CLS with other HIV-positive partners. Higher sexual disclosure was more common among GBMSM who had CLS with other HIV-positive partners only (72.1%) compared to those who had higher-risk CLS with HIV-serodifferent partners (55.6%), other CLS with HIV-serodifferent partners (45.9%), or condom-protected sex only (47.6%). Findings suggest mutual HIV-disclosure and HIV-serosorting were occurring in this population. Knowledge of VL status may have impacted on disclosure to sexual partners.